Yoshimasa and the Silver Pavilion : the creation of the soul of Japan - Keene, Donald (Asia perspectives., 2003)
During Yoshimasa's reign, the aesthetic taste of the Japanese was shaped: the nõ theater flourished, Japanese gardens were developed, and the tea ceremony had its origins in a small room at the Silver Pavilion. Flower arrangement, ink painting, and shoin-zukuri architecture began or became of major importance under Yoshimasa. Poets introduced their often barely literate warlord-hosts to the literary masterpieces of the past and taught them how to compose poetry. Even the most barbarous warlord came to want the trappings of culture that would enable him to feel like a civilized.